Reconstructing Anti-Corruption Education Through the Principle of Good Faith: A Civil Law Perspective on Integrity Formation in Indonesian Law School - Iskandar Zulkarnaen; Zamalludin Sembiring (Law and Justice research journal, 2026)
Corruption remains a multidimensional challenge caused not only by weaknesses in law enforcement but also by declining integrity among public officials and legal professionals. Although anti-corruption education has been integrated into higher education in Indonesia, its implementation largely emphasizes criminal law compliance rather than the cultivation of ethical values. This study aims to reconstruct anti-corruption education in Indonesian law faculties by positioning the civil law principle of good faith as its ethical foundation. The research employs doctrinal legal research using statutory, conceptual, philosophical, and comparative approaches. Data were collected from legislation, legal doctrines, scholarly literature, and national and international legal instruments, and analyzed through legal interpretation, conceptual analysis, and normative legal reasoning. The findings reveal that the principle of good faith under Article 1338(3) of the Indonesian Civil Code embodies honesty, fairness, responsibility, loyalty, and respect for the legitimate interests of others. These values align with international integrity standards, including the United Nations Convention against Corruption (UNCAC) and the OECD Public Integrity Framework. Based on these findings, the study proposes a Good Faith-Based Anti-Corruption Education Model consisting of value, conceptual, and institutional reconstruction. The study contributes a novel perspective by reconceptualizing good faith from a contractual doctrine into the ethical foundation of integrity-oriented legal education, providing a theoretical framework for curriculum reform, sustainable corruption prevention, and the promotion of good governance in Indonesia. ng public officials and legal professionals. Although anti-corruption education has been incorporated into higher education institutions across Indonesia, its implementation continues to be dominated by a criminal law perspective that emphasizes punitive legal compliance rather than the systematic cultivation of integrity. This study aims to reconstruct anti-corruption education within Indonesian law faculties by positioning the civil law principle of good faith as the ethical foundation for integrity-oriented legal education. The research adopts a doctrinal legal research methodology using four complementary approaches: the statutory approach, conceptual approach, philosophical approach, and comparative approach. The analysis is based on legislation, legal doctrines, scholarly literature, and national and international legal instruments concerning public integrity and corruption prevention. Data were analysed through legal interpretation, conceptual analysis, and normative legal reasoning. The findings demonstrate that the principle of good faith, as codified in Article 1338(3) of the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata), extends beyond its conventional contractual function and should be understood as a general principle of law embodying honesty, fairness, responsibility, loyalty, and respect for the legitimate interests of others. These values closely correspond to internationally recognized integrity standards reflected in the United Nations Convention against Corruption (UNCAC), the OECD Public Integrity Framework, and Indonesia's anti-corruption education policies. Building upon these findings, the study develops a Good Faith-Based Anti-Corruption Education Model consisting of three interrelated stages: value reconstruction, conceptual reconstruction, and institutional reconstruction. The model integrates the principle of good faith with character education, legal culture, and public integrity to establish an integrity-oriented framework for legal education within Indonesian law faculties. The principal novelty of this study lies in reconceptualizing good faith from a doctrine of contract law into the ethical foundation of anti-corruption education. By expanding the preventive function of civil law beyond the regulation of private legal relationships, the proposed model offers a new theoretical framework for strengthening integrity-oriented legal education, supporting curriculum reform, and contributing to sustainable corruption prevention and the development of good governance in Indonesia.